Kesesuaian Tujuan, Perilaku Disfungsional Rekan Kerja, Asimetri Informasi sebagai Prediktor Disfungsional Bawahan (Studi Empiris pada Manajer Pemasaran) - Se Tin . (Jurnal Akuntansi, 2006)
This paper reports the results of a study that developed and tested a causal model of dysfunctional behavior among a large sample of marketing managers. The results indicate that three contextual variables (goal congruence, perceived peer dysjfunctional behavior and information asymmetry between superiors & subordinates)predicts, in varying degrees, the extent of person-role conflict and job tension experienced by the managers. In turn, role conflict increases job tension and job tensions increases the extent of dysfunctional behavior. However, no effects for theperson-role conflict/dysfimctional behavior link were found.Key words: Dysfunctional behavior, management control